Maternal co-relates of anaemia among children aged 1-3 years of age in a rural area of Meerut - Bano, Tanveer; Agarwal, Abhishek; Garg, Sunil Kumar; Chopra, Harivansh; Jain, Seema; Singh, Ganesh (International Journal Of Community Medicine And Public Health, 2018)
Background: Iron deficiency anaemia constitutes more than half of the anaemia burden among the under 5 children. In addition to socio-demographic factors, the maternal factors plays an important role in determining childhood anaemia. The objective of the study was to determine the prevalence of anaemia among 1-3 year old children and to find their association with maternal factors. Methods: The present cross sectional study was conducted in a sub centre village under Machhra CHC. Sample size was calculated as 182 by taking the prevalence of anaemia as 79% with 7.5% relative precision and 95% confidence interval. From the list of 404 children obtained from MCTS data, 200 children were selected randomly. Detailed information regarding socio demographic factors and maternal factors was obtained on a pre tested and pre designed questionnaire. Hemoglobin levels were estimated using haemo check rapid diagnostic kit. The data was collected and analyzed on epi info 3.7.2 using appropriate statistical tests. Results: Out of 200 children 77.5% of them were suffering from mild to severe anaemia. Among all the maternal factors studied maternal education, iron folic acid consumption during pregnancy, birth order of the index case and history of exclusive breast feeding were found to be significantly associated with prevalence of anaemia among the children. Conclusions: The present study revealed a high prevalence of anaemia in children and maternal factors plays an important role in determining the disease.